2017
DOI: 10.1021/acsami.7b14330
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Poly(lactic-co-glycolic acid)-Magnetic Microspheres Prepared by Rotating Membrane Emulsification for Transcatheter Arterial Embolization and Magnetic Ablation in VX2 Liver Tumors

Abstract: Interventional embolization is a popular minimally invasive vascular therapeutic technique and has been widely applied for hepatocellular carcinoma (HCC) therapy. However, harmful effects caused by transcatheter arterial chemoembolization (TACE) and radioembolization, such as the toxicity of chemotherapy or excessive radiation damage, are serious disadvantages and significantly reduce the therapeutic efficacy. Here, a synergistic therapeutic strategy combined transcatheter arterial embolization and magnetic ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…The experimental use of PLGA MSs for hepatic artery embolization has been reported [18]. PLGA is a copolymer that can be hydrolyzed into biocompatible substances, including lactic acid and glycolic acid monomers [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental use of PLGA MSs for hepatic artery embolization has been reported [18]. PLGA is a copolymer that can be hydrolyzed into biocompatible substances, including lactic acid and glycolic acid monomers [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that PLGA MSs releases drugs slowly into surrounding tissues through a diffusion mechanism to promote the complete release of the drug, thereby improving the treatment effect of drugs [32]. TACE combined with magnetic PLGA MSs significantly enhanced the delivery of cytotoxic drugs to rabbit liver tumors while reducing the systemic toxicity in the animals [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to finely tune size and composition of PLA and PLGA MP by adopting proper multiple emulsification processes affords fabrication of complex composite particles. In this regard, a rotating membrane emulsification system was employed for the preparation of iron nanoparticle loaded PLGA MP for tumor arterial embolization and magnetic ablation (Liang et al 2017).…”
Section: Membrane Emulsificationmentioning
confidence: 99%
“…Yi‐Jun Liang et al . prepared PLGA‐magnetic microspheres by rotating membrane . Shear induced dissociation coupling with ultrafiltration (SID‐UF), is a novel method to selectively recover metals and complexant according to the difference of shear stabilities of polymer‐metal complexes .…”
Section: Introductionmentioning
confidence: 99%